2012
DOI: 10.1590/s1517-83822012000300032
|View full text |Cite
|
Sign up to set email alerts
|

Selection of thermophilic and thermotolerant fungi for the production of cellulases and xylanases under solid-state fermentation

Abstract: Twenty-seven thermophilic and thermotolerant fungal strains were isolated from soil, decaying organic matter and sugarcane piles based on their ability to grow at 45°C on medium containing corn straw and cardboard as carbon sources. These fungi were identified in the genera Aspergillus, Thermomyces, Myceliophthora, Thermomucor and Candida. The majority of the isolated strains produced xylanase and cellulases under solid state fermentation (SSF). The highest cellulase and xylanase productions were obtained by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 33 publications
2
56
0
8
Order By: Relevance
“…Moreover, 80% of the optimum activity was obtained at pH range of 3.5 to 5.0. Other studies reported an acid optimum pH for xylanase from A. fumigatus strains (MORETTI et al, 2012;SOUZA et al, 2012). Optimum temperature was observed at 60 °C, suggesting that this xylanase can be a thermophilic enzyme which can be useful for many biotechnological processes which operate at high temperatures ( Figure 3B).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Moreover, 80% of the optimum activity was obtained at pH range of 3.5 to 5.0. Other studies reported an acid optimum pH for xylanase from A. fumigatus strains (MORETTI et al, 2012;SOUZA et al, 2012). Optimum temperature was observed at 60 °C, suggesting that this xylanase can be a thermophilic enzyme which can be useful for many biotechnological processes which operate at high temperatures ( Figure 3B).…”
Section: Resultsmentioning
confidence: 82%
“…The fungus Aspergillus fumigatus is a widespread species commonly found in agricultural residues with numerous biotechnological applications. Previous studies reported its ability to produce secondary metabolites with antimicrobial activity (ARAÇARI et al, 2002), and many enzymes such as proteases, cellulases and xylanases (OYELEKE et al 2010;MORETTI et al, 2012;SOUZA et al, 2012). In this work, a thermotolerant A. fumigatus SCB4 strain isolated from sugarcane bagasse piles from Brazilian Cerrado was evaluated for the production of extracellular xylanase.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations